2020
DOI: 10.3390/agronomy10101566
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Induced Effects on Productivity, Zinc Use Efficiency, and Grain Biofortification of Bread Wheat under Different Tillage Permutations

Abstract: Zinc (Zn) deficiency is a global concern for human health and causes a decrease in crop production and nutritional characteristics. A two-year field study was planned to evaluate comparative effects of various Zn application approaches in bread wheat under plough tillage (PT) and zero tillage (ZT) system. Cultivation of wheat under ZT improved the soil organic carbon (17%), total soil porosity (11%), soil microbial biomass nitrogen (5%), and carbon (5%) in comparison to PT system averaged across the two years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 70 publications
4
23
0
Order By: Relevance
“…Zinc deficiency has been associated with pollen infertility and reduced seed productivity in wheat and lentil ( Pandey et al, 2006 ; Cakmak, 2008 ; Zulfiqar et al, 2020 ). Unlike the high-level NPs (>1,000 mg L –1 ), at lower levels, no visible toxic symptoms on cells or tissues of reproductive organs were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency has been associated with pollen infertility and reduced seed productivity in wheat and lentil ( Pandey et al, 2006 ; Cakmak, 2008 ; Zulfiqar et al, 2020 ). Unlike the high-level NPs (>1,000 mg L –1 ), at lower levels, no visible toxic symptoms on cells or tissues of reproductive organs were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the food fortification approach has been broadly adopted. Furthermore, previous studies found that Zn biofortification in wheat has improved grain quality and caused to reduce the Zn deficiency among people (21)(22)(23)(24)(25)(26)(27)(28). However, past literature has shown that economic efficiency is lower due to Zn deficiency, thereby increasing the mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…The Zn concentration was measured in the digest by an atomic absorption spectrophotometer (PerkinElmer, Analyst 100, Waltham, United States). Agronomic Zn use efficiency (ZUE) was calculated as described by Zulfiqar et al (2020) :…”
Section: Methodsmentioning
confidence: 99%